The verdict : inside story of Shrimati Indira Gandhi's case with unabridged judgment - Grover, K. L. (Legend Publications, 1975)
On the Allahabad High Court judgement which declared void the 1971 election of Indira Nehru Gandhi, b. 1917, to the Lok Sabha from Rae Bareli constituency, Uttar Pradesh; includes documents.